Bgp2, a new member of the carcinoembryonic antigen-related gene family, encodes an alternative receptor for mouse hepatitis viruses. - Nédellec, P (1994)
Murine coronaviruses such as mouse hepatitis virus (MHV) infect mouse cells via cellular receptors that are isoforms of biliary glycoprotein (Bgp) of the carcinoembryonic antigen gene family (G. S. Dveksler, C. W. Dieffenbach, C. B. Cardellichio, K. McCuaig, M. N. Pensiero, G.-S. Jiang, N. Beauchemin, and K. V. Holmes, J. Virol. 67:1-8, 1993). The Bgp isoforms are generated through alternative splicing of the mouse Bgp1 gene that has two allelic forms called MHVR (or mmCGM1), expressed in MHV-susceptible mouse strains, and mmCGM2, expressed in SJL/J mice, which are resistant to MHV. We here report the cloning and characterization of a new Bgp-related gene designated Bgp2. The Bgp2 cDNA allowed the prediction of a 271-amino-acid glycoprotein with two immunoglobulin domains, a transmembrane, and a putative cytoplasmic tail. There is considerable divergence in the amino acid sequences of the N-terminal domains of the proteins coded by the Bgp1 gene from that of the Bgp2-encoded protein. RNase protection assays and RNA PCR showed that Bgp2 was expressed in BALB/c kidney, colon, and brain tissue, in SJL/J colon and liver tissue, in BALB/c and CD1 spleen tissue, in C3H macrophages, and in mouse rectal carcinoma CMT-93 cells. When Bgp2-transfected hamster cells were challenged with MHV-A59, MHV-JHM, or MHV-3, the Bgp2-encoded protein served as a functional MHV receptor, although with a lower efficiency than that of the MHVR glycoprotein. The Bgp2-mediated virus infection could not be inhibited by monoclonal antibody CC1 that is specific for the N-terminal domain of MHVR. Although CMT-93 cells express both MHVR and Bgp2, infection with the three strains of MHV was blocked by pretreatment with monoclonal antibody CC1, suggesting that MHVR was the only functional receptor in these cells. Thus, a novel murine Bgp gene has been identified that can be coexpressed in inbred mice with the Bgp1 glycoproteins and that can serve as a receptor for MHV strains when expressed in transfected hamster cells.